Agrarian Contracts in Retrospect: Two Bihari Villages in 1970 - Clive Bell (University of Heidelberg, Department of Economics, 2016)
The object of this essay is to describe and analyse contractual relations in two villages in North-east Bihar at a time when the so-called `green revolution' promised much and the region had just started to benefit from canal irrigation. It is against this historical background that I will examine, with the benefit of hindsight, the functioning of the markets for labour and tenancies, and their interplay with those for draught power and credit. Theory sheds much light on why such richly diverse arrangements prevailed, but despite notable subsequent advances, it still leaves certain important questions without a fully satisfactory answer.
urn:nbn:de:bsz:16-heidok-221705
Keywords: J43; N55; O13; Q15; 330; agrarian contracts; Bihar